Prenatal use of cleaning and scented products and its association with childhood asthma, asthma symptoms, and mental health and developmental comorbidities. (2nd January 2021) - Bably, Morium; Arif, Ahmed A.; Post, Abigail
Abstract: Introduction: Occupational use of cleaning chemicals has been related to asthma in adults. However, little information is available on the effect of non-occupational use of cleaning products during pregnancy on childhood asthma. This study examines the association between prenatal exposure to cleaning and scented products with childhood asthma, asthma symptoms, and mental and developmental comorbidities among low-income families in Karachi, Pakistan. Methods: Four hundred children from the Koohi Goth Women's Hospital were included in the study. Parents' or guardians reported current asthma, asthma-related symptoms, mental health problems, and behavioral problems among the children. Multivariable logistic regression analysis was used to examine the association between the use of cleaning and scented products during pregnancy and seven different outcome variables. Results: The odds of nocturnal cough were significantly elevated among children whose mothers reported the use of cleaning products ( OR: 2.23, 95% CI: 1.15–4.31) or scented products (OR: 2.15, 95% CI: 1.22–3.77) during pregnancy. Mental health comorbidities were threefold elevated (OR: 3.05, 95% CI: 1.74–5.35) among children whose mothers reported using scented products during pregnancy. There was no statistically significant association of the prenatal use of cleaning or scented products with current asthma status or nocturnal symptoms of wheezing, shortness of breath, and chest tightness among children. Conclusions: The study results indicate prenatal exposure to cleaning and scented products is associated with nocturnal cough among children. The study also suggests an association between prenatal use of scented products and mental health comorbidities among children.